Lymphangioleiomyomatosis and multifocal micronodular pneumocyte hyperplasia in Japanese patients with tuberous sclerosis complex - Tanaka, Mari; Hirata, Haruhiko; Wataya-Kaneda, Mari; Yoshida, Mitsuhiro; Katayama, Ichiro (Respiratory investigation, 2016)
Abstract Background Pulmonary involvement in tuberous sclerosis complex (TSC) includes lymphangioleiomyomatosis (LAM) and multifocal micronodular pneumocyte hyperplasia (MMPH). This retrospective study investigated pulmonary involvement in Japanese TSC patients and pulmonary function testing in TSC-LAM. Methods The study subjects included 59 TSC patients (age range: 13–66, 15 males and 44 females). Female patients were divided into 3 groups (Group 1: symptomatic LAM, Group 2: asymptomatic LAM, Group 3: without LAM) and 3 cystic grades according to increasing cyst numbers on computed tomography images (patients without LAM, Grade 1 patients, and Grade 2+Grade 3 patients). The results of pulmonary function tests were compared among the groups and the grades. Results One male (6.7%) patient and 19 female (43.2%) patients were diagnosed with LAM and 7 male (43.2%) and 23 female (52.3%) patients were diagnosed with MMPH. Patients with multiple pulmonary nodules had higher rates of renal angiomyolipoma and history of seizures than patients without nodules. Although all 6 adolescent patients displayed no pulmonary symptoms, MMPH was found in 3 patients and LAM was found in a 13-year-old girl. Carbon monoxide diffusing capacity (DLco) differed significantly among the 3 groups and DLco and carbon monoxide diffusing capacity divided by the alveolar volume (DLco/VA) differed significantly among the 3 cystic grades. Conclusions There was no difference in the prevalence of pulmonary involvement in TSC patients among countries. LAM and MMPH occur even during adolescence in TSC patients. DLco and the number of cysts are useful predictors of onset and progression of TSC-LAM.